Shoot density and biomass fluctuation of seagrass from Merambong shoal - Zahari, Mohd. Naziruddin (2013)
A study on vegetative morphology and diversity of seagrass with monitoring cover, shoot density and biomass was carried out at Merambong shoal (N 01° 19’ 50.9”, E 103° 36’ 45”), Johore, Malaysia from March to August 2013 during low tide. Line-transect and quadrat methods were used for obtaining the mentioned seagrass diversity. A percentage of cover was recorded in the field while shoot density and biomass data was processed in the laboratory from 3 random sub-samples of quadrats. A total of 8 seagrass species; Enhalus acoroides, Thalassia hemprichii, big-leaved Halophila ovalis, small-leaved H. ovalis, H. spinulosa, Cymodocea serrulata, Halodule pinifolia and narrow-leaved H. uninervis were identified at Merambong shoal. The higher no of species per quadrat recorded are 1-7 species. A smaller species e.g., H. ovalis produce higher cover (small-leaved H. ovalis 6.00-39.49% and big-leaved H. ovalis 6.72-30.81%) when compared to larger species (e.g., E. acoroides 3.17-7.52%). Big-leaved H. ovalis was the dominant species with 64.63 percent of contribution. Small-leaved H. ovalis was the highest shoot density 5608.33 shoot/m2 and big-leaved H. ovalis had highest biomass (AG 86.78 g DW m-2, BG 36.29 g DW m-2) compared to other species. In this study, strong correlation between above-ground and below-ground DW biomass ratio was recorded (r=0.845) for linear leaves and (r=0.835) for rounded leaves.